The Literacy Development of Primary School Level Students : an Investigation of Teaching and Learning in Rural Area. - Wulandari, Retno; Drupadi, Intan Dewi; Anggraeni, Evi Ayu (Prosiding University Research Colloquium, 2021)
Literacy is very important to be developed from an early age. Literacy is the initial ability that must be possessed by every individual to live life in the future. The literacy rate of children in rural areas is lower than in urban areas. So literacy even in rural areas must be cultivated so that the literacy culture in rural communities is not left behind and is useful in realizing the role of the younger generation in aspects of state development. To develop literacy, the roles of parents and teachers must work together in monitoring, facilitating, and motivating